ETIKA BISNIS ISLAM PADA PRAKTIK OPERASIONAL INDOMARET KOTA SURABAYA - Vina Fauziyah; Mustofa Mustofa (Jurnal Ekonomi Bisnis dan Kewirausahaan, 2025)
Indomaret, as a modern retail network in Surabaya, operates under a Standard Operating Procedure (SOP) that regulates cashier services, inventory management, employee governance, and customer facilities. This study aims to examine the extent to which these operational practices align with Islamic business ethics, particularly the principles of shidq (honesty), ‘adl (justice), amanah (trustworthiness), mas’uliyyah (responsibility), and maslahah (public benefit). The research employed a descriptive qualitative approach through observation, interviews, and documentation. The findings reveal that Indomaret’s operations attempt to apply Islamic ethics by ensuring price transparency, equal service for all customers, responsible inventory management, regulatory compliance, and limited CSR initiatives. Nevertheless, implementation remains inconsistent due to varying standards across outlets, limited social contributions, and a dominant profit-oriented approach. Moreover, the Surabaya City Government’s free parking policy at minimarkets has not been fully effective, as illegal parking attendants continue to impose charges on customers. The study concludes that while Islamic business ethics principles are being applied, stronger internal monitoring, employee ethics training, and collaboration with local authorities are required to ensure that Indomaret’s operational practices fully comply with Islamic values and contribute to public welfare.